Fast Facts: Cardiac Arrhythmias - Kaye, Gerry; Furniss, Steve; Lemery, Robert (S. Karger, 2013)
Recent progress in interventional therapies has revolutionized the management of cardiac arrhythmias, resulting in a remarkable improvement in outcomes for patients. Yet the diagnosis and management of arrhythmias are still viewed as a complex and inaccessible area of modern cardiology. 'Fast Facts: Cardiac Arrhythmias' cuts through the technical detail to provide a better understanding of how the patient with arrhythmia presents, and how the problem should be best investigated and managed. Highlights include:• Succinct descriptions with clear well-annotated illustrations of normal conduction and the mechanisms of arrhythmias• A simple classification of arrhythmias based on 12-lead ECG patterns• A comprehensive review of presenting signs and symptoms, with key questions to ask the patient• A logical approach to investigation: predict it (history and examination), wait for it (monitoring) or provoke it (electrophysiological testing)• Practical information on management options: pharmacological therapy, direct cardioversion, catheter ablation and cardiac devices• The latest international guidelines on atrial fibrillation and catheter and surgical ablation• Important pharmacological updates, including the latest thinking on anticoagulation.This highly readable handbook is a practical resource for all primary care physicians, cardiologists in training, cardiac nurses, technicians and medical students seeking a better understanding of the mechanisms of arrhythmias and the contemporary therapies available, with a view to improving patient care.Contents:• Conduction within the heart• Classification and mechanisms of arrhythmias• Presenting signs and symptoms• Investigation• Management principles• Supraventricular arrhythmias• Atrial flutter• Atrial fibrillation• Ventricular arrhythmias• Rare and unusual arrhythmias• Cardiac devices: Pacemakers and defibrillators• Useful resources
Keywords: kardiovaskulární systém; kardiologie; srdeční arytmie; Cardiovascular System; Arrhythmias, Cardiac